2008
DOI: 10.1111/j.1540-8159.2008.01073.x
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Effects of Cardiac Resynchronization Therapy in Chronic Heart Failure: Benefits in Patients with Preserved Exercise Capacity

Abstract: Improvement in functional status is associated with restoration of neurohormonal reflex control at medium term. Less depressed functional status (peak VO(2)) was the strongest predictor of responders to CRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 44 publications
4
14
0
Order By: Relevance
“…In our study, V̇ E /V̇CO 2 significantly decreased post-CRT as has been previously reported (1315). However, the contributions of the components of the alveolar gas equation to the observed decline of V̇ E /V̇CO 2 have not been previously shown.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, V̇ E /V̇CO 2 significantly decreased post-CRT as has been previously reported (1315). However, the contributions of the components of the alveolar gas equation to the observed decline of V̇ E /V̇CO 2 have not been previously shown.…”
Section: Discussionsupporting
confidence: 91%
“…As we did not know the initial HRV and HRT parameters in CRT patients, we assumed that they had been improved with functional status. This assumption was strongly supported with the previous studies (13)(14)(15)(16) showing improved HRV and HRT parameters in CRT responders. Similarly, an improvement might be achieved in ICD patients with a placebo effect.…”
Section: Study Limitationssupporting
confidence: 80%
“…In studies, which investigated HRV and HRT parameters in CRT patients, improvement of functional capacity was accompanied with the improvement of HRV and HRT parameters in good responders to CRT (13)(14)(15)(16). However, we do not know whether there is an additional benefit of CRT on autonomic functions independent from the improvement in functional capacity.…”
Section: Introductionmentioning
confidence: 89%
“…Several studies have provided further insights into the clinical role of BRS in heart failure by showing that cardiac resynchronisation therapy (CRT), through its mechanical and haemodynamic effects on the left ventricle, is able to reduce cardiac sympathetic afferent activity thus improving BRS [16,17]. Furthermore, in a group of 32 patients studied 1 day after implantation and with the CRT device either on or off, CRT acutely increased BRS.…”
Section: Clinical Valuementioning
confidence: 99%